창원시 소재 한의원 종사자의 에니어그램 성격유형에 따른 직무만족도 연구 - 이정원(Jeong Won Lee) (동의생리병리학회지, 2012)
The purpose of this study was to examine Enneagram personality types and job satisfaction of Korean medicine clinic staff, thereby providing basic materials for job training programs and human resource management programs for Korean medicine clinic staff with a lot of face-to-face relationship. The researcher visited 50 Korean medicine clinics randomly selected from 255 clinics in Changwon and explained the purpose of this study and the content of questionnaire. Questionnaires on Enneagram personality types and job satisfaction were distributed to and collected from those who consented to participate. Data analysis was done using SPSS WIN IBM 20.0 program. The results are as follows. General characteristics of the subjects were as follows. Female respondents comprised 97.6% of the total. The rate of those whose age was between 20 and 25, between 26 and 30, between 31 and 35, between 36 and 40, between 41 and 45, and 46 years old or older was 22.6%, 21.4%, 13.1%, 21.4%, 17.9%, and 3.6%, respectively. The rate of those who were unmarried was 46.4%. As for educational levels, those who graduated from high school or received lower level education, those who graduated from two-year college, and those who graduated from university accounted for 46.4%, 39.3%, and 14.3%, respectively. Regarding the distribution of the center of energy, 64.3% was in the instinctive center, 20.3% in the thinking center, and 15.5% in the emotional center. As for the personality type of Enneagram, 25.0% belonged to type 8, 22.6% to type 9, 15.5% to type 1, 9.5% to type 5, 8.3% to types 4 and 6, 6% to type 2, and 2.4% to types 3 and 7. Job satisfaction according to the center of energy and personality types was not statistically significantly different. Interpersonal relationship, autonomy, and overall job satisfaction according to the developmental stage of Enneagram were significantly different.